Life Path of Therese Dalberg (1866–1893) to Recovery. Pilgrimage to Lourdes in France (Theatrum historiae, 2019)
In the year 2017, the authors of this article published a book called The Life and Works of Therese Dalberg. The Noble Poetess from the Castle of Dačice where they captured the life of this young noblewoman. Unfortunately, they were not able to find out the cause of her death and so Therese's fight against the illness was still shrouded in mystery. However, the presented article should uncover some of unanswered questions related to Therese’s path to recovery, including her stays in various European spas, mainly in Lourdes in France. Most of Therese's life was connected with unending pain, paralysing her body, and seeking solace in God, giving her hope for recovery. Not only Therese, but also the whole family of Dalberg put hope in a pilgrimage place in Lourdes, where Therese travelled with her sisters. This unique pilgrimage became inseparable part of lthe whole family's life. Therefore it is described in detail in this study. Sadly, in spite of all the effort, Therese’s life could not be saved and she passed away before her 27th birthday in 1893.
Keywords: the Dalbergs; Lourdes; pilgrimage; recovery; illness; faith in God; miracle